The effect of systemic intraoperative warming on cardiac function of patients after off-pump coronary bypass grafting (术中综合保温措施对非体外循环下冠状动脉搭桥术患者心功能的影响) - CHANG Jia (常佳); HUANG Jing (黄静) (中西医结合护理)
Objective To investigate the effect systemic intraoperative warming on cardiac function of patients after off-pump coronary bypass grafting (OPCABG). Methods A total of 530 patients undergoing OPCABG were enrolled and divided into two groups. The contral group (n=240) was treated with normal preoperative nursing, and the warming group (n=290) was treated with the systemic intraoperative warming, especially using the IOB forced-air warming system. Swan-Ganz catheter was inscerted to mornitor the cardiac function. The blood temperature and the hemondynamics were recorded at pre-operation, after operation, pre-extubation and before extracting Swan-Ganz catheter. Results The duration of tracheal intubation and staying in ICU decrease significantly in the warming group (P<0. 05); the incidence of malignant arrthemia in the warming group was lower than that in the control group (P＜0. 01). The incidence of low body temperature in the warming group was lower than that in the control group(P＜0. 01). The cardiac index (CI) of the control was lower than that of the warming group at the end of operation, and the systemic vascular resistance index (SVRI) of the control was higher than that of the warming group, with a significant difference (P<0. 05). The CI of the control group increased gradually until the Swan-Ganz catheter had been removed, while the SVRI of the warming group had been steady in the whole protocol. Conclusion The treatment of systemic intraoperative warming in the patients of OPCABG can decrease the risk of low body temperature, speed up the recovery of cardiac function, decrease the duration of tracheal intubation and staying in ICU. It should be expended in preoperative nursing. (目的 探讨术中综合保温措施对非体外循环下冠状动脉搭桥术(OPCABG)后患者心功能恢复的影响。方法 将进行OPCABG的530例患者分为对照组(n=240)和保温组(n=290)。对照组采用常规手术护理方法, 保温组采取术中综合保温措施并使用IOB充气升温装置, 以肺动脉漂浮导管监测患者心功能变化。分别于手术开始、手术结束、气管拔管前、拔漂浮导管4个时间点观察血温数值及血流动力学参数变化。结果 保温组较对照组气管插管持续时间及监护室停留时间下降, 差异有统计学意义(P<0. 05); 保温组较对照组术中恶性心律失常发生率下降, 差异有统计学意义(P＜0. 01)。术中低体温发生率保温组低于对照组, 差异有统计学意义(P＜0. 01)。手术结束即刻, 保温组较对照组心指数(CI)升高, 外周血管阻力指数(SVRI)对照组较保温组升高, 差异有统计学意义(P<0. 05)。对照组患者CI直至拔除漂浮导管前才逐渐升高, 保温组SVRI在整个监测过程中保持平稳。结论 OPCABG患者术中采取综合保温护理措施, 能有效减少低体温的发生, 有助于心功能恢复, 缩短术后气管插管时间, 减少患者监护室停留时间, 值得作为围手术期护理常规进行推广。)